2019
DOI: 10.1007/s11121-019-0977-y
|View full text |Cite
|
Sign up to set email alerts
|

Financial Incentives for Promoting Participation in a School-Based Parenting Program in Low-Income Communities

Abstract: Although financial incentives are a well-accepted strategy for raising parent participation rates in prevention studies, they are rarely employed in practice due to concerns about their ethics, sustainability, and public acceptability. We sought to address these common concerns in the context of a larger prevention study using financial incentives to boost parent participation in a group-based parenting program implemented in an urban school district. We examined the extent to which the financial incentives de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 45 publications
3
12
0
Order By: Relevance
“…PPs experiencing social marginalization may need to overcome multiple barriers to participation. For individuals living on low incomes, financial honoraria upfront can promote participation and reduce attrition over the course of a project ( Gross and Bettencourt 2019 ). A patient-oriented project is emergent by design; however, patient partnerships in the middle of a pandemic require an even greater degree of flexibility and agility in order to engage with marginalized populations.…”
Section: Effective Engagement Of Diverse and Inclusive Patient Communities For Equitable Patient Partnershipsmentioning
confidence: 99%
“…PPs experiencing social marginalization may need to overcome multiple barriers to participation. For individuals living on low incomes, financial honoraria upfront can promote participation and reduce attrition over the course of a project ( Gross and Bettencourt 2019 ). A patient-oriented project is emergent by design; however, patient partnerships in the middle of a pandemic require an even greater degree of flexibility and agility in order to engage with marginalized populations.…”
Section: Effective Engagement Of Diverse and Inclusive Patient Communities For Equitable Patient Partnershipsmentioning
confidence: 99%
“…A systematic review found that monetary incentives can increase enrolment in parenting programs and initial attendance rates but not retention (Gonzalez et al, 2018). Gross and Bettencourt (2019) found that 71% of low-income parents in their study cited cash incentives as a motivation to enroll, and that attendance rates of those parents were higher, but the quality of participation was unrelated to whether incentives motivated enrolment. Rodriguez et al (2020) found that parents in their monetary incentive condition were more engaged in sessions than those in the program-as-usual condition but not more inclined to enroll.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, only 14.2% of participants in ELLAS listed "financial reimbursement" as one of their top three reasons for participating in the study. A study investigating motivations for participating in a school-based parenting program in Latinx and low-income communities found that intrinsic motivation and benefits from the program outweighed the incentive of receiving extra money to attend these sessions [37]. One study that investigated motivations of German women for participation in a clinical trial for menstrual pain found financial incentives less important than an interest in finding alternative solutions to dealing with pain and furthering research in a field that affects participants [38].…”
Section: Discussionmentioning
confidence: 99%